Aplicación de la pena natural en los delitos culposos y el derecho a la libertad individual del procesado. - Gaibor, Doris X. (2022)
The natural penalty is a legal instrument that allows the judge to stop imposing a penalty in cases in which the offender as a result of their actions. unlawful acts is physically or psychologically affected, not being necessary to impose a state penalty, this instrument has been legislated in Ecuador in the Organic Comprehensive Criminal Code since 2014, which is an advance for Ecuadorian criminal law, however the way in which that is currently legislated has generated a doubt about its effectiveness which has motivated the present investigation in which doctrinal studies have been made on topics such as punishment, its purposes, the nature of natural punishment, constitutional principles and criminal law, In addition, the legislation of Colombia, Mexico, Argentina has been reviewed to verify the way in which it is legislated in them and a comparative study has been made with the Ecuadorian legislation, in addition, judges and legal professionals have been interviewed regarding the way in which that natural punishment is legislated in our country. After all this work, some gaps and limitations have been detected, ranging from the crimes in which this institution is applicable to the issue of the victims who are considered for its application, therefore, the urgent need to reform the Article 372 of the Ecuadorian criminal norm that legislates the legal institution studied.